PERENCANAAN JARINGAN DISTRIBUSI AIR BERSIH PERUMNAS BANYUMANIK KOTA SEMARANG - Rio Dessika Finanda; Saefudin Nurhuda; Abdul Kadir; Salamun Salamun (Jurnal Karya Teknik Sipil, 2013)
With the increasing number of residents in the area Banyumanik, then the rank of the need for clean water needs of the population will also rise. Then the distribution network planning needs to be done to improve public services and Semarang in the current period and future. Development of water supply systems for the necessary existence of the concept of planning, designing, implementing, and operating a mature work by considering the social, economic, physical state area, and urban land use. This study aims to determine the water needs until 2021. Analysis of pressure and continuity performed with theoretical analysis and program Epanet as controls, customized to the needs of water every hour.mThe planning construction of water distribution networks in the form of the amount of data required and the conditions of residence as a basis for planning. Projections of future population growth can be calculated from the rate of population growth the last 5 years ie 2007 s / d 2011, obtained data from the Central Bureau and Statistics. And projected population growth is calculated using the geometric method, so that can be projected on the population in the city of Semarang Banyumanik Housing until 2021 amounted to 45.309 people. Need for clean water the planning criteria can be based on water table of DPU Human Settlements, the calculation of the population in 2021 Housing Banyumanik average - average of 98 liters / second and the need for clean water at the peak 147 liters / second. Analysis and planning of water distribution using the program Epanet 2.0. Results from analysis and planning, distribution network to run smoothly until the year 2021 it was replacement of existing piping system that is not enough with PVC pipe along the 715 m Ø250, Ø250 PVC pipe along the 610 m, pipe Ø250 PVC along 199 m. Total budget proposed for the development of water distribution networks in the National Housing Authority Banyumanik is Rp.1.028.000.000, 00. With long work for 24 weeks.